Danhong Injection Attenuates High-Fat–Induced Atherosclerosis and Macrophage Lipid Accumulation by Regulating the PI3K/AKT Insulin Pathway. Issue 2 (August 2019) - Zhou, Mingxue; Ren, Pan; Li, Sinai; Kang, Qunfu; Zhang, Ying; Liu, Weihong; Shang, Juju; Gong, Yanbing; Liu, Hongxu
Abstract : Background and Aims: High-fat diet (HFD) is reported to induce atherosclerosis and insulin resistance. Macrophage lipid accumulation has been implicated as key mediators during the development of HFD-induced atherosclerosis. Traditional Chinese formula, which has long been used to improve disorder of glucose and lipid metabolism of patients, is now gradually being used as complementary therapy. This study aimed to investigate the effect of Danhong injection (DHI), a Chinese medicine used for the treatment of coronary artery disease, on atherosclerosis and its underlying mechanisms. Methods and Results: We observed the effects of DHI on HFD-induced atherosclerosis in a mice model, macrophage lipid accumulation in an ox-LDL–stimulated macrophage model, and the role of PI3K/AKT insulin pathway in the process of DHI ameliorating atherosclerosis. The data demonstrated that DHI attenuated atherosclerosis by ameliorating blood lipids, reducing the atherosclerotic index and atherosclerotic plaque area in HFD-induced atherosclerotic mice, and inhibiting TC levels in an ox-LDL–induced macrophage model. By estimating the levels of serum insulin resistance–related indexes and protein expression of GLUT-4, DHI treatment dramatically inhibited the levels of fasting serum NEFA and fasting serum insulin and promoted the protein expression of GLUT-4 in aortas of the HFD-induced atherosclerotic mice. Moreover, according to the hints provided by microarray-based transcriptional profiling, the results demonstrated that DHI treatment also promoted the activation of PI3K/AKT insulin signaling pathway induced by IRS-1 in aortas of HFD-induced atherosclerotic mice. Furthermore, in an ox-LDL–induced macrophage model, the activation of PI3k/AKT signaling pathway also effectively functioned in the process of DHI inhibiting macrophage lipid accumulation. Conclusions: These results highlight that DHI treatment attenuates atherosclerosis and macrophage lipid accumulation by promoting the activation of PI3K/AKT insulin signaling pathway. It provides new insights into the molecular mechanism of DHI and its therapeutic potential in the treatment of atherosclerosis. Abstract : Supplemental Digital Content is Available in the Text.